State of the Art: Carbon Emission Accountability Modeling - Lo, Valencia; Potdar, Vidyasagar (Conference Publishing Services, 2010)
Global warming is becoming a big problem and carbon emissions from a variety of sources are the cause of it. To control emission, a number of carbon emission reduction policies and schemes such as the Kyoto Protocol & COP15 treaty have been reached and put in place. However, not all countries participate in these global carbon mitigation treaties. One of the many reasons for the absence of participation in developing countries is due to their incapable financial status. As in the case of developed countries such as the USA, it is usually due to monetary profiting before and after the participation and the ambiguous carbon emission responsibility that each country has to bear. Many accounting models have already been proposed in the current literature to solve the problem of responsibility ambiguity. However, the current accountability models are proposed for the general industries and not for the ICT industry.We feel that these models cannot be applied directly to the ICT industry since factors of influence are significantly different. In ICT industry, it involves a mix of international and national factors such as accountability issues (eg. the party responsible for the carbon emission) and the implications of participants and non-participants of those climate change mitigation treaties in different countries. Hence, taking into account all the determinant factors and different stakeholders involved in the process of the carbon accounting, we are proposing an efficacious and fair accountability model for the ICT industry in our research. This accountability model can be used to assist Government worldwide in coming up with a fair tax `relief/subsidy' scheme for ICT companies for more sustainable business models. This research will take a science and engineering approach and the outcome of this research would be significant to the global combat against climate change.